(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Sikkim is rich in hydropower potential in spite of its small area. National Hydroelectric Power Corporation Limited (NHPC) and other private developers are entering in hydropower sector of Sikkim. Though some of local people are in the protest of dams, the Government of Sikkim is hopeful and determines to achieve benefit largely from hydropower Keywords: Sikkim, Himalayas, hydropower, environment doi: 10.3126/hn.v3i0.1919 Hydro Nepal Journal of Water, Energy and Environment Issue No. 3, July 2008. Page: 38-41